STRUCTURE AND CONTENT OF THE MODEL OF TRAINING FOR MARATHON RUNNERS, TAKING INTO ACCOUNT THE FEATURES OF THE MECHANISM OF ENERGY SUPPLY OF MUSCLE ACTIVITY - Bakaev V.V. ,; Bolotin A.E. ,; Vasilyeva V.S. ,; Tikhonov L.Yu. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop the structure and content of a training model for marathon runners, taking into account the peculiarities of the mechanism of energy supply of muscle activity and to evaluate its effectiveness. Methods and structure of the study. Twenty-three marathon runners from Russia aged 23 to 37 were examined. Runners specialized in marathon running. Preparation for the competition took place in two groups of athletes: "aerobic type" and "mixed type" energy supply of muscle activity. Means and methods of training were selected taking into account the peculiarities of the mechanism of energy supply of their muscular activity. Results and conclusions. In the course of the study, it was found that the content of the marathon runners training model, taking into account the peculiarities of their mechanism of energy supply of muscular activity, should be formed from the standpoint of a systemic and program-targeted approach to the selection of training means and methods. Training sessions, taking into account the peculiarities of the mechanism of energy supply of muscle activity, solve problems not only associated with the development of physical qualities in marathon runners, but also with a number of positive morphological changes in the structure of their muscles, ligaments and joints, as well as in improving the mechanism of energy supply of muscle activity. For the training of marathon runners, it is typical to solve special problems for the development of tempo and speed endurance. As a result of the application of the experimental methodology of training in athletes, a significant increase in the indicators of the functional and reserve capabilities of the body was revealed.